Clinic-epidemiological characterization of COVID-19 positive cases in Cienfuegos municipality. - Luis Enrique Jiménez Franco; Dianelys Maria Gutierrez Pérez; Tamara Montenegro Calderón; Niurys González Cano (Universidad de Ciencias Médicas de Granma, 2021)
Introduction: the new coronavirus called SARS-CoV2 that causes the COVID-19 disease emerged in the city of Wuhan, Hubei province, China. The number of confirmed cases rose to alarming numbers. The World Health Organization declared it an urgent international health emergency. Objectives: to characterize the confirmed cases of COVID-19 in the municipality of Cienfuegos during the month of March 2021. Materials and method: an observational, descriptive, retrospective cross-sectional study of confirmed COVID-19 cases in the municipality of Cienfuegos in March 2021 was carried out. The universe consisted of 320 cases and the sample of 158. The variables used age, sex, health area, symptoms, number of contacts. Statistical statistics of absolute frequency and percentage relative were used. Results: the female sex represented 53.16% (84 cases). The 50-59 group stood out with 32 cases (20.25%). Health area II had 37 cases (24%). Fever was the outstanding symptomatology (47.63% equivalent to 75 cases). The group of representative contacts was that of 10 to 19 (74 cases for 46.87%). Conclusions: there were no significant differences regarding sex; but yes regarding age groups. The cases reported in area II demonstrate the need for more rigorous measures; although the existing ones contributed to reducing the number of contacts per patient. The symptoms had heterogeneous behavior; although patients with feverish symptoms stood out.